2020
DOI: 10.1002/lary.28729
|View full text |Cite
|
Sign up to set email alerts
|

Discharge by Noon: A Checklist Initiative by the Otolaryngology Service

Abstract: Objectives/Hypothesis Hospital length of stay (LOS) and throughput are critical issues for hospitals. Late hospital discharges contribute to bottlenecks in the emergency department, overcrowd surgical and procedural areas, and limit patient tertiary‐care center transfers. Our goal was to increase discharge by noon (DCBN) percentage from 8% to over 50% in a sustainable manner. Study Design Retrospective Review. Methods We used a multiple time series design and a quality improvement approach. An interdisciplinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Currently, the only published otolaryngology-specific discharge checklist aims to improve the number of discharges by noon by refining structural hospital characteristics. 23 This checklist has many benefits but did not show an improvement in 30-day readmissions. In another study, Revell et al 24 generated a physiological scoring system to help determine readiness for discharge in otolaryngology patients.…”
Section: Discussionmentioning
confidence: 96%
“…Currently, the only published otolaryngology-specific discharge checklist aims to improve the number of discharges by noon by refining structural hospital characteristics. 23 This checklist has many benefits but did not show an improvement in 30-day readmissions. In another study, Revell et al 24 generated a physiological scoring system to help determine readiness for discharge in otolaryngology patients.…”
Section: Discussionmentioning
confidence: 96%
“…The primary outcome of this analysis is an aggregate of unplanned hospital readmission or presentation to the ED within 30 days of discharge. Early TOD, which was defined as discharge before noon in concordance with other analyses in the medical and surgical literature, 6,7,[10][11][12] was a secondary outcome.…”
Section: Outcome Measurementioning
confidence: 99%
“…2,3,[15][16][17][18] Data on these effects in patients undergoing elective surgery are less clear. 4,6,19,20 Our analysis of TOD after inpatient admission after elective anterior cervical surgery is the only known assessment of early TOD in spine surgery. In that analysis, we demonstrated that, when controlling for numerous covariates, TOD was not associated with increased risk of readmission to the hospital or re-presentation to the emergency department (ED) within 30 days of surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,[13][14][15][16] Similar trends have not necessarily been observed in the context of surgical admissions, although effects are mixed. 4,9,17,18 Specific data regarding the efficacy of such approaches in the context of spine surgery are lacking. As such, in this analysis, we sought to assess the impact of time of discharge (TOD) on readmission after elective spine surgery in a contemporary patient cohort at a large academic medical center.…”
mentioning
confidence: 99%